Strengthening Critical Thinking of Elementary School Students through Android-Based iSpring Suite Interactive Media - Purnomo Indra Saputra; Ivayuni Listiani; Heny Kusuma Widiyaningrum; Supri Wahyudi Utomo (LP. Ma'arif Janggan Magetan, 2024)
The purpose of this study is to explore the integration of technology in education, especially the use of iSpring Suite as a learning medium that supports the development of students' critical thinking skills. This study uses a literature review method by analyzing various empirical studies and relevant academic sources related to the use of educational technology and the development of critical thinking. The results of the analysis indicate that critical thinking is an important cognitive skill that allows students to analyze problems, consider multiple perspectives, and draw logical conclusions. In addition, the use of iSpring Suite in teaching through animated content and interactive quizzes has been shown to increase student motivation and engagement. The conclusion of this study is that the use of technology-based learning media such as iSpring Suite can create a more conducive, interactive, and effective learning environment, and support a deeper understanding of the material than conventional lecture methods. The implications of these findings indicate that educators need to be trained to develop and apply interactive media optimally to improve the quality of learning. Further research is recommended to test the effectiveness of the use of iSpring Suite empirically in various subject contexts and educational levels, and evaluate its impact on improving learning outcomes and developing 21st century skills more comprehensively.